Effects of tabata body weight training on body fat percentage in obese women - Siti Maesaroh; Septyaningrum Putri Purwoto; Dendi Novendri (Jurnal Maenpo : Jurnal Pendidikan Jasmani Kesehatan dan Rekreasi, 2022)
This study aims to prove the effect of an exercise protocol on the percentage of body fat tested in obese women. The samples of this study were 16 women, aged 19-21 years, had a Body Mass Index (BMI) = 25.0-29.9 kg/m² according to the Asia Pacific criteria. The sample was taken from the Department of Psychology, Faculty of Education (FIP), Surabaya State University (UNESA). This type of research uses a pre-experimental research design with "the one group pretest-posttest group design". This research was conducted for 4 weeks with the implementation of exercise 1 week 5 times. Body fat percentage was measured using a Bioelectrical Impedance Analysis (BIA) SECA medical Body Composition Analyzer (mBCA) which has a type specification of 514. The mean results and standard deviation of the pretest were 42.31±3.74%; posttest 41.24±4.03%, paired t-test results obtained p= 0.000, and the percentage of delta (%∆) experienced a decrease in body fat percentage 2.57±2.16%. The conclusion of this study shows the effect of tabata body weight training in reducing body fat percentage in obese women.Key words: Tabata, Body weight training, Obesity